Uncoupling global and fine-tuning replication timing determinants for mouse pericentric heterochromatin - Wu, Rong (The Rockefeller University Press, 2006)
Mouse chromocenters are clusters of late-replicating pericentric heterochromatin containing HP1 bound to trimethylated lysine 9 of histone H3 (Me3K9H3). Using a cell-free system to initiate replication within G1-phase nuclei, we demonstrate that chromocenters acquire the property of late replication coincident with their reorganization after mitosis and the establishment of a global replication timing program. HP1 dissociated during mitosis but rebound before the establishment of late replication, and removing HP1 from chromocenters by competition with Me3K9H3 peptides did not result in early replication, demonstrating that this interaction is neither necessary nor sufficient for late replication. However, in cells lacking the Suv39h1,2 methyltransferases responsible for K9H3 trimethylation and HP1 binding at chromocenters, replication of chromocenter DNA was advanced by 10–15% of the length of S phase. Reintroduction of Suv39h1 activity restored the later replication time. We conclude that Suv39 activity is required for the fine-tuning of pericentric heterochromatin replication relative to other late-replicating domains, whereas separate factors establish a global replication timing program during early G1 phase.